2019
DOI: 10.1101/772749
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Complex multi-trait responses to multivariate environmental cues in a seasonal butterfly

Abstract: Developmental plasticity in a seasonal environment allows an organism to optimally match its life-history traits with the fluctuating conditions. This critically relies on abiotic and biotic factors, such as temperature or food quality, that act as environmental cues and predict seasonal transitions. In most seasonal environments, multiple factors vary together, making it crucial to understand their combined effects on an organism’s phenotype. Here, we study plasticity in a multivariate environment in the butt… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Laboratory studies have characterized thermal reaction norms for various traits (e.g., Oostra et al, 2011). Revealingly, lab thermal phenotypes do not include phenotypes as extreme as those seen in nature, where other variables combined with temperature might affect development outcomes (Bauerfeind and Fischer, 2005;Rodrigues et al, 2018;Singh et al, 2019), but do include intermediate phenotypes between the typical dry-and wet-season forms, which are rarely found in nature (Brakefield and Reitsma, 1991;Windig et al, 1994;Muller et al, 2019). Lab studies have also allowed characterization of the physiological and genetic basis of thermal plasticity.…”
Section: Phenotypic Plasticity and Climate Changementioning
confidence: 99%
“…Laboratory studies have characterized thermal reaction norms for various traits (e.g., Oostra et al, 2011). Revealingly, lab thermal phenotypes do not include phenotypes as extreme as those seen in nature, where other variables combined with temperature might affect development outcomes (Bauerfeind and Fischer, 2005;Rodrigues et al, 2018;Singh et al, 2019), but do include intermediate phenotypes between the typical dry-and wet-season forms, which are rarely found in nature (Brakefield and Reitsma, 1991;Windig et al, 1994;Muller et al, 2019). Lab studies have also allowed characterization of the physiological and genetic basis of thermal plasticity.…”
Section: Phenotypic Plasticity and Climate Changementioning
confidence: 99%
“…Hence, plastic responses to one type of environmental stress may be dependent on the state of another external factor. Such non-additive multidimensional plasticity, in response to combinations of thermal and nutritional environments, has been demonstrated in moths [14], butterflies [18] and fruit flies [19]. For example, Singh et al showed that poor host plant quality mainly influenced development at intermediate temperatures the tropical butterfly Bicyclus anynana [18].…”
Section: Introductionmentioning
confidence: 99%
“…Such non-additive multidimensional plasticity, in response to combinations of thermal and nutritional environments, has been demonstrated in moths [14], butterflies [18] and fruit flies [19]. For example, Singh et al showed that poor host plant quality mainly influenced development at intermediate temperatures the tropical butterfly Bicyclus anynana [18]. Moreover, significant genetic variation for (multidimensional) plasticity is known to exist in both natural and laboratory populations [20-22].…”
Section: Introductionmentioning
confidence: 99%